Moyamoya Disease and Hemiplegic Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
A 6-year-old girl presenting with a 6-month history of classical familial migraine, complicated by transitory hemiparesis and moyamoya disease diagnosed by MRI, is reported from the Kaiser Permanente Medical Center, Hayward, CA.